Lectura comprensiva para el desarrollo del pensamiento crítico - Cajia Changoluisa, Johnny David (2020)
The present research wok is in the Educational Center the Sower located in the Parish San Juan de Pastocalle, with the purpose of responding to the following problem, How to influence comprehensive reading in the development of critical thinking ?, the same as deploying as objective, improve the low level of reading and promote the critical thinking of the students. The type of research was exploratory in which the deductive method affected with its techniques was used, this has served to structure the epistemological foundations on comprehensive reading and its influence on the development of critical thinking, as well as to structure and validate a proposal that manages to solve the problem detected. To meet the objective, five comprehensive reading methodological strategies are needed which are the applications helped students to competent readers and framed with the qualities of a critical thinker. These strategies were aimed at developing the five levels of reading that helped develop critical thinking skills in students. After the proposal was developed, it was validated and executed with short results; the acquisition of new working methodologies for the teacher, creation of the habit of reading and interest on the part of the students, better performance in the acquisition of learning and, finally and better reading performance in terms of the literal and inferential level, in the end instance improved the way students communicate.